Sperm activate TLR2/TLR1 heterodimerization to induce a weak proinflammatory response in the bovine uterus - Mansouri, Alireza; Yousef, Mohamed Samy; Kowsar, Rasoul; Usui, Nonoka; Akthar, Ihshan; Miyamoto, Akio (Frontiers in Immunology, 2023)
Toll-like receptor 2 (TLR2) signaling pathway is involved in the sperm-triggered uterine inflammatory response at insemination, but its precise mechanism at molecular-level remains unknown. According to the ligand specificity, TLR2 forms a heterodimer with TLR1 or TLR6 as an initial step to mediate intracellular signaling, leading to a specific type of immune response. Hence, the present study aimed to identify the active TLR2 heterodimer (TLR2/1 or TLR2/6) that is involved in sperm-uterine immune crosstalk in bovine using various models. First, in-vitro (bovine endometrial epithelial cells, BEECs) and ex-vivo (bovine uterine explant) models were employed to test different TLR2 dimerization pathways in endometrial epithelia after exposure to sperm or TLR2 agonists; PAM3 (TLR2/1 agonist), and PAM2 (TLR2/6 agonist). Additionally, in-silico approaches were performed to confirm the dimer stability using de novo protein structure prediction model for bovine TLRs. The in-vitro approach revealed that sperm triggered the mRNA and protein expression of TLR1 and TLR2 but not TLR6 in BEECs. Moreover, this model disclosed that activation of TLR2/6 heterodimer, triggers a much stronger inflammatory response than TLR2/1 and sperm in bovine uterine epithelia. In the ex-vivo model that mimics the intact uterine tissue at insemination, sperm also induced the protein expression of both TLR1 and TLR2, but not TLR6, in bovine endometrium, particularly in uterine glands. Importantly, PAM3 and sperm induced similar and low mRNA expression of pro-inflammatory cytokines and TNFA protein to a lesser extent than PAM2 in endometrial epithelia. This implied that sperm might trigger a weak inflammatory response via TLR2/TLR1 activation which is similar to that of PAM3. Additionally, the in-silico analyses showed that the existence of bridging ligands is essential for heterodimer stability in bovine TLR2 with either TLR1 or TLR6. Altogether, the present findings revealed that sperm utilize TLR2/1, but not TLR2/6, heterodimerization to trigger a weak physiological inflammatory response in the bovine uterus. This might be the way to remove excess dead sperm remaining in the uterine lumen without tissue damage for providing an ideal uterine environment for early embryo reception and implantation.